Jean Liébault (1535–1596), médecin hippocratique : vers la gynécologie moderne - Bourbon, Florence (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2010)
While Hippocrates’ gynaecological treatises were entirely translated into Latin in 1525, thus breaking the silence to which Galen had confined them, and while the entire gynaecological knowledge accumulated until the Renaissance kept circulating in the Gynaeciorum libri, Liébault published in 1582 a large treatise entitled Trois livres appartenant aux infirmitez et maladies des femmes and renamed Thresor des remedes secrets pour les maladies des femmes in 1585. It was a translation of Giovanni Marinello’s work. Liébault’s choice, together with his foreword and his personal comments scattered throughout the translation, particularly regarding the uterus and menstruation, highlights his Hippocratic rather than Galenic viewpoint, thus contributing to the emergence of modern gynaecology.